Intra-Articular Polyacrylamide Hydrogel Injections Are Not Innocent - Murat Tonbul; Mujdat Adas; Taner Bekmezci; Ahmet Duran Kara (Case Reports in Orthopedics)
Osteoarthritis is a chronic disorder characterized by joint cartilage degeneration with concomitant changes in the synovium and subchondral bone metabolism. Many conservative treatment modalities, one of which is intra-articular injections, have been described for the treatment of this disorder. Traditionally, hyaluranic acid and corticosteroids are the agents that have been used for this purpose. Recently, polyacrylamide hydrogels are being used widely. Biocompatibility, nonbioabsorbability, and anti-infectious effect obtained by silver addition made polyacrylamide hydrogels more popular. In this paper, we present a case and the method of our management, in whom host tissue reaction (foreign body granuloma, edema, inflammation, and redness induration) has been observed, as the first and unique adverse effect reported in the literature.